Group Decision Support System for Job Promotion Using the Simple Additive Weighting (SAW) Method - Dizani, Muhar; Sumiati, Sumiati; Suherman, Suherman (Journal of Machine Learning and Soft Computing, 2019)
The Group Decision Support System is a tool used to help group decision makers become faster and more objective. A case study at Serang Raya University is the selection of employees for promotion. The problem is the difficulty in determining which employees will be promoted to fill a certain position and spend a lot of time and how to do the calculation? The research methodology used is system analysis, and calculation of the Simple Additive Weighting (SAW) method. The criteria chosen are based on staffing policies. The decision makers involved were the dean of the faculty, the head of the staffing department and the university's rector. Simple Additive Weighting (SAW) can determine the weight value for each attribute, then proceed with the ranking process that will select the best alternative from a number of alternatives. The results are used to make it easier for users to choose the employees to choose for promotion. This system is expected to help speed up employee decision making to be promoted.